Detection of Adenoviruses (AdV) in Culture-Negative Environmental Samples by PCR during an AdV-Associated Respiratory Disease Outbreak - Echavarria, Marcela (American Society for Microbiology, 2000)
Since 1954, adenoviruses (AdV) have been recognized as an important cause of acute respiratory disease (ARD) among U.S. military recruits. Until recently, routine oral vaccination for AdV serotypes 4 and 7 eliminated epidemic AdV-associated ARD in this population. Now that the manufacturer has ceased production, vaccination has ended and AdV epidemics have reappeared. As part of a prospective epidemiological study during the high-risk ARD season, serial samples were obtained from ventilation system filters and tested for AdV by culture and PCR. An outbreak occurred during this surveillance. Of 59 air filters, 26 (44%) were AdV positive only by PCR. Sequence analysis confirmed the presence of AdV serotype 4, the implicated outbreak serotype. The number of AdV-related hospitalizations was directly correlated with the proportion of filters containing AdV; correlation coefficients were 0.86 (Pearson) and 0.90 (Spearman's rho). This is the first report describing a PCR method to detect airborne AdV during an ARD outbreak. It suggests that this technique can detect and quantify AdV-associated ARD exposure and may enable further definition of environmental effects on AdV-associated ARD spread.